2019
DOI: 10.1007/s11031-018-09750-w
|View full text |Cite
|
Sign up to set email alerts
|

Motivated level of construal: How temperature affects the construal level of state-relevant stimuli

Abstract: Motivation affects perception, for example when people overestimate the psychological proximity of goal-relevant objects. Additionally, proximity maps onto more concrete (vs. abstract) construal. Following from these findings, we predicted that people construe goal-relevant stimuli more concretely than goal-irrelevant stimuli. Three experiments tested this idea (total N = 305). In Experiment 1, people who were warm (versus cold) grouped cold drinks into more and narrower categories, as cold drinks served their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The items were presented in random order (Cronbach’s α = .83 [Study 1a] and .82 [Study 1b]). Although the BIF was originally developed to measure individual differences (Vallacher & Wegner, 1989), it can also be used as a validation measure for abstraction manipulations (e.g., Freitas et al, 2004; Hansen & Steinmetz, 2019; Liberman & Trope, 1998; Liviatan et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The items were presented in random order (Cronbach’s α = .83 [Study 1a] and .82 [Study 1b]). Although the BIF was originally developed to measure individual differences (Vallacher & Wegner, 1989), it can also be used as a validation measure for abstraction manipulations (e.g., Freitas et al, 2004; Hansen & Steinmetz, 2019; Liberman & Trope, 1998; Liviatan et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that good service climate may have an impact on employees' job satisfaction (Schneider et al, 2003), while a general negative affect may result from a poor climate appraisal (Schmit and Allscheid, 1995;Rhodes et al, 2016;Hansen and Steinmetz, 2019). The study assumes that positive entrepreneurial emotion is the emotional reaction to the optimism appraisal processes, while negative entrepreneurial emotion is the emotional reaction to overconfidence.…”
Section: Relationship Between Cognitive Bias and Entrepreneurial Emotionmentioning
confidence: 99%
“…Some scholars have applied this theory to the empirical research of employee attitude and behavior (Kruglanski et al, 2015;Rhodes et al, 2016;Hansen and Steinmetz, 2019). However, no scholars have introduced the model into the study of entrepreneurship psychology.…”
Section: Self-regulating Attitude Theorymentioning
confidence: 99%
“…In a related vein, a growing body of evidence suggests that perception can be altered by top-down processes, such as emotions 28 , actions 29 , and motivations 30 , with studies pointing out a specific influence on the perception of physical distance. For instance, the act of wearing a heavy backpack can make us perceive distance as greater 31 , as can throwing a heavy ball 32 .…”
Section: Introductionmentioning
confidence: 99%